Assessing and evaluating human-wildlife interactions for coexistence in shared landscapes - Ferraz, Katia Maria Paschoaletto Micchi de Barros; Bento, Isabella de Freitas; Di Souza, Anna Beatriz Queiroz; Nunes, Caio da Silveira; Guimarães, Maria Augusta de Mendonça; Pereira, Monicque Silva; da Silva, Livia Lima; de Campos, Letícia Keiko Nunes; Gobbi, Anita Seneme; Alves, José Caio Quadrado; Alvarez, Loisa Fabrícia Prates; Marchini, Silvio; et al. (Frontiers in Conservation Science, 2025)
Land sharing strategies for conciliating biodiversity conservation and human development usually do not consider the need to deal with human-wildlife conflicts, a type of human-wildlife interaction (HWI). To measure, monitor and solve conflicts is fundamental to achieve the coexistence necessary to promote environmental and social justice. Here, we present a new approach to assess and evaluate HWI aiming to inform decision-making regarding conflicts. We developed a method to classify and map events between humans and wildlife according to their nature, context and effect for both sides, distinguishing what an encounter (unidirectional) is and what an interaction (bidirectional effect) is. We typified and categorized HWI regarding their effects (positive or negative) for both sides. We compiled opportunistic observations from events between humans and wildlife in a shared landscape (campus Luiz de Queiroz, Piracicaba, São Paulo, Brazil) from February 2022 until April 2024. We created a standardized table, performed descriptive statistics, used Minimum Bounding Geometry and Kernel Density, a simple method idealized to assist scientists and managers in different contexts. We had a total of 570 events, of which 297 were characterized as encounters and 273 as HWI. We recorded 42 animal taxa related to the events, of which 36 interacted with humans, being Nasua nasua, Cairina moschata, and Didelphis albiventris the most frequent ones. We identified 16 types of HWI that can occur in shared landscapes, 10 were categorized as Human-Wildlife Conflict, six as Unsustainable Use, four as Wildlife Damage and three as Convivencia, with some classified in more than one category. Among them, 10 occurred in our studied landscape with Unintentional Feeding being the most frequent one. We classified for the first time Unexpected Encounter, Accident Avoidance and Chase Away as HWI. Spaces of interaction were close to main buildings, central lawn and cats’ feeding sites. Our approach was useful to prioritize species and stakeholders, and to identify the large amount of food supply due to inadequate waste disposal and domestic cat feeding as the primary reason for most of HWI in our studied landscape. We recommend a comprehensive characterization of HWI to find interconnections and guide strategies for coexistence.